Examining food sources in the city of Tamale, Ghana - Karg, H.; Akoto-Danso, Edmund K.; Drechsel, Pay (2015)
This empirical study examines food sources and their quantitative contribution to the city of Tamale, Ghana. The results contribute to an understanding of the urban food system, and evoke questions relating to the standardised measurement and evaluation of urban food system resilience across geographical contexts.